ANALISIS DETERMINAN INTENSI BERWIRAUSAHA MAHASISWA JURUSAN AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS BRAWIJAYA - UMASITA HARDHINI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The study aims at finding out the extent to which Accounting Department students of University of Brawijaya have entrepreneurial intentions and the factors which influence such intentions. This explanatory research applies quantitative approach and Linan model as the application of TPB (Theory of Planned Behavior). The data are collected from 110 samples out of the population of Accounting Department students who have takenentrepreneurship course and are analized by multiple regression method. The results of the study indicate that the entrepreneurial intentions are positively and significantly influenced by personal attraction / attitude and perceived behavioral control. In addition, perceives social norms (subjective norms) per se do not give direct effect on the entrepreneurialintention; but together with personal attraction and perceived behavioral control, they can positively influence the intentions. Keywords: Entrepreneurial Intentions, Theory of Planned Behavior (TPB), Entrepreneur, Accounting Students